A complete harvest: the future of rice as bioenergy - Tanger, Paul, speaker and filmmaker; Unidentified speaker (Colorado State University. Libraries, 2013)
Communicating science to different groups of society is a critical need. Beyond basic research which seeks knowledge, applied research attempts to address real world issues; both aspects of scientific research can be highlighted. In order to give our research a broad audience and highlight the motivation, collaboration, and potential benefit of our research, I conceived and directed a short documentary of one of my research projects. Footage was shot both at the field site in the Philippines, and on the Colorado State University campus, along with interviews of some of the key collaborators.
Accessibility features: Unedited transcript.
To request an edited transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: rice; environmental variation; bioenergy; correlation